The Impact of an Ethnomathematics Intervention on Sixth Graders’ Perceptions about the Nature of Mathematics - Khanafer, Heba (2023)
The purpose of this study was to explore the impact of teaching an ethnomathematical unit about areas and perimeters on sixth graders’ perceptions about the nature of mathematics in a private school in Kuwait. The focus of the study was on students’ perceptions about the nature of mathematics in terms of its connectedness to culture and real life in addition to the role of mathematics education in promoting social and political values. Ethnomathematics, as defined by D’Ambrosio, is the mathematics practiced by different cultures; it reflects their practices, their ways of living, and their social values. In the past decades, more mathematics educators, researchers, and experts started to show interest in teaching ethnomathematics because of the dry, abstract, and boring mathematics instruction followed in most mathematics classrooms. Ethnomathematical interventions done in many classrooms showed positive results on students’ experience in learning mathematics whether on their motivation, achievement, or perceptions towards mathematics. This study employed a qualitative case study that drew upon classroom observations, interviews, and students’ activity sheets. Twenty-two grade six students participated in the study through random sampling. Twelve students were interviewed according to their achievement levels. Data from transcribed observations and interviews and data from activity sheets were analyzed through qualitative thematic analysis. Data from different sources were triangulated and compared to increase the reliability of the study results. Findings revealed that teaching an ethnomathematical geometry unit had a great impact on students’ perceptions towards the nature of mathematics. Eight essential themes were derived from data analysis which are the following: mathematics as culturally and historically produced; mathematics connected to real life; mathematics connected to values; mathematics connected to other subjects; eurocentrism and cultural superiority; students’ interest, motivation, and collaboration; students’ pride in their culture; and girls’ empowerment and gender stereotypes breakage. Although this study was limited to a specific groups of female sixth graders in a private school in Kuwait, the results raised new questions for future research. Few recommendations were provided for stakeholders, curriculum designers, and mathematics teachers.